2021
DOI: 10.1155/2021/9100444
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Suppresses Annulus Fibrosus Cell Apoptosis through Regulating Oxidative Stress Reaction in an Inflammatory Environment

Abstract: During disc degeneration, the increase of inflammatory cytokines and decrease of disc cell density are two prominent features. Enhanced inflammatory reaction contributes to disc annulus fibrosus (AF) cell apoptosis. In this study, we investigated whether resveratrol can suppress AF cell apoptosis in an inflammatory environment. Rat disc AF cells were cultured in medium with or without tumor necrosis factor-α (TNF-α). Resveratrol was added along with the culture medium supplemented with TNF-α. Caspase-3 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…33−35 Oxidative stress after AF injury can cause cell apoptosis and ECM degradation and further hinder AF repair. 36 The main endogenous biological antioxidants of the body include SOD, CAT, glutathione peroxidase, glutathione reductase, peroxidase reductase, etc. SOD and CAT are the main anti-ROS enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33−35 Oxidative stress after AF injury can cause cell apoptosis and ECM degradation and further hinder AF repair. 36 The main endogenous biological antioxidants of the body include SOD, CAT, glutathione peroxidase, glutathione reductase, peroxidase reductase, etc. SOD and CAT are the main anti-ROS enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive accumulation of ROS can act on biological macromolecules and destroy cellular structure. Oxidative stress is involved in the pathogenesis of many diseases, including IDD. Oxidative stress after AF injury can cause cell apoptosis and ECM degradation and further hinder AF repair . The main endogenous biological antioxidants of the body include SOD, CAT, glutathione peroxidase, glutathione reductase, peroxidase reductase, etc.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The naturally occurring nonflavonoid polyphenol resveratrol (3,5,4′-trihydroxy-trans-stilbene) ( Figure 1 ) is a phytoalexin, produced as a stress response in plants for their protection against fungal infections [ 240 , 241 ]. It can be isolated from the roots of the herbaceous perennial plant Polygonum cuspidatum of the knotweed and buckwheat family Polygonaceae, but its presence has also been documented in trees (i.e., eucalyptus and spruce), in flowering plants (i.e., the lily species Veratrum grandiflorum and Veratrum formosanum ), in peanuts and groundnuts and in grapevines, grapes and red wine [ 242 , 243 , 244 ].…”
Section: Plant-derived Compounds With a Reported Senotherapeutic Acti...mentioning
confidence: 99%
“…In nature, resveratrol can be found in cis- and trans-isomers, with the latter forms being the more biologically active due to the lower steric hindrance of their side chains [ 244 ]. Resveratrol’s health benefits have long been recognized because numerous studies have shown its protective effects against various diseases, such as cancer, ischemic disease, neurodegenerative diseases, cardiovascular diseases, diabetes and OA [ 240 , 242 , 244 ], as well as its ability to increase lower organisms’ lifespan and to generally improve the health of mammals [ 245 ]. The wide protective effect of resveratrol on different cell types is mediated by several signaling pathways and molecules, including NF-κB, MAPK, COX-2, AMPK and p53, that regulate its anti-inflammatory, anti-aging, anti-cancer and cartilage-protective properties [ 246 , 247 ].…”
Section: Plant-derived Compounds With a Reported Senotherapeutic Acti...mentioning
confidence: 99%
See 1 more Smart Citation